Analysis of the archive management problems in islamic boarding schools in supporting the administration of islamic education institutions - Zaidatul Arifah; Lutvia Rizki Andini; Elva Lestari; Muhammad Fatah Dhya Ulchaq; Muhammad Ulfan Afandi; Saqib Amar Mutaqin; Suyatno Ladiqi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This research is a qualitative study with a case study design that aims to reveal various problems in archive management in the pesantren environment and explore solutions that can support the improvement of the administrative quality of Islamic education institutions. The research focus was directed at two pesantren with different characteristics, namely Pesantren X (modern) and Pesantren Y (salaf), in order to obtain a contextual and in-depth understanding. The problems identified include technical, structural, and limited human resources aspects in the archival process. Data were obtained through in-depth interviews, observation of administrative activities and archival systems, and analysis of available documents. The results showed that both pesantren faced similar challenges, such as the absence of a standardised archive classification system, limited storage facilities, not maximising archive digitisation, and the lack of understanding of archival principles among administrative staff. However, strategic solutions have begun to be implemented, including through human resource training, the preparation of archive management SOPs, strengthening archival institutions, and implementing simple digital systems for efficient data access. This research provides a comprehensive overview of the challenges and solutions in archive management, and confirms the importance of revamping the archive system to improve administrative effectiveness and accountability in the pesantren environment. Good archive management is not only a technical necessity, but part of the strategic efforts of pesantren in maintaining their existence, preserving history, and providing quality Islamic education services.